Financial health and management practices: a multi-year cross country analysis of PLCs. Issue 3 (2nd July 2018) - Hasan, Md Shamimul; Omar, Normah; Hassan, ABM Rashedul
Abstract : Purpose: The purpose of this study is to examine the relationship between financial strength or condition and managerial practices in preparing financial statements of public limited companies. The objectives of this study are threefold – to measure the financial strength, to measure integrity index and to examine the relationship between management practices and financial strength. Design/methodology/approach: Financial ratios, Altman's Z-Score, integrity index, ranking approach and chi-square test are used to achieve the objectives. A multi-year cross-country analysis is done by considering sample of seven Asian countries, namely, Malaysia, Singapore, Thailand, Indonesia, Hong Kong, China and Japan. Findings: The study catches the relationship between management practices and financial strength across sample countries. Management practices is one of the responsible factors for this relationship. They use discretionary power in preparing financial statements to control the trading results. The principles of accounting do not support the alteration of financial data to look the company better on paper. The cost of financial statement fraud is higher than other occupational fraud. Research limitations/implications: This study does not cover factors other than management practices and further study could be conducted to look for the other reasons that may also responsible for the deviations. Practical implications: Conflict of interest between shareholders and board of directors is not a new phenomenon. Auditing system is introduced to minimize this conflict of interest, but they failed to uphold their position in reality. Management also needs to prove their integrity in financial statements. Ethical consideration is the highest priority. Social implications: Stakeholders, especially regulators, professional bodies and academics, should concentrate on the issue on 'how to reduce the manipulation in financial statements' to create a safe investments avenue for the nation. Originality/value: This study provides empirical evidences regarding the influence of management practices on financial statements and financial strength of listed companies across countries. The culture, attitudes, beliefs, perceptions, etc., are different from country to country. The aim is to contribute empirical evidence about the relationship between management practices and financial health in different settings. This study is first of its kind.